PENERAPAN MANAJEMEN PEMBELAJARAN BERBASİS DARİNG DENGAN MENGGUNAKAN APLİKASİ GOOGLE CLASSROOM UNTUK MENİNGKATKAN KEMAMPUAN MAHASİSWA DALAM MEMBUAT PERANGKAT PEMBELAJARAN - Sri Hartatik; Nafiah, Nafiah (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2020)
Learning-based activities can be done effectively with efficient learning management systems. Theaim is to determine the application of online-based learning management by using the google classroomapplication to improve the ability of students to make learning administration in learning planning in theprimary education study program Nahdlatul Ulama University of Surabaya. The research method usingclassroom action research (CAR) was carried out in primary education study program Nahdlatul UlamaUniversity of Surabaya, thirth semester B class with a total of 56 students. This research method usesclassroom action research with four stages, namely planning, action implementation, observation, andreflection. Data collection techniques using checklist and observation. The data analysis technique usesdescriptive quantitative. The results showed the application of online-based learning management by usingthe google classroom application to improve the ability of students to make learning tools in learning planningcourses at primary education study program Nahdlatul Ulama University of Surabaya. proved to be veryeffective in improving the ability of students to compile elementary learning tools. This is seen from theincrease in each cycle and the average value of students is more than the specified indicator achievementcriteria. In the first cycle to the 1st meeting, the average value of the preparation of elementary school learningadministration (Annual program, semester program, syllabus, lesson plan) was around 45, while at thesecond meeting the average value of the learning equipment was around 68.25. Whereas in the second cycleat the 1st meeting the average value of the preparation of learning devices was around 73.5, whereas at thesecond meeting the average value of students in the preparation of the elementary learning tools was 96.75.